PENGHIJAUAN DALAM UPAYA MENINGKATKAN PEDULI LINGKUNGAN DI DESA BOIDU KECAMATAN BULANGO UTARA KABUPATEN BONE BOLANGO - Supriatna, Supriatna; Safitri, Ikraeni (Universitas Gorontalo, 2024)
Cultivation activities are activities from cultivated forests that cover large areas and the skills required are sufficient. Planting includes species selection, field preparation, stake installation, planting hole making, seed transportation, shelter. The purpose of this activity is as an activity in the tridharma of higher education, one of which is community service) and also to raise awareness in the village community about the importance of planting so that it can increase the type of vegetation and the role of plants in absorbing CO2 gas and storing groundwater. This activity will be carried out in 2022 starting from the stages of activity planning and implementation of coaching in Boidu Village. The results obtained are that it can increase the type of plant vegetation in the village so that the environment can become cooler, besides that with the presence of plants, the process of absorbing water by plants can reduce air surface runoff. Planting is carried out using wood-producing species and non-timber forest products so that in the future it can be utilized by the community in the form of fruits produced by plants.Â Keywords : Boidu Village, Greening, Planting